al-I'lal in Surah al-Nur: The Morphological Analysis and Its Use in Teaching Morphology (Ilm al-Sharf) - Siti Mufarokah; Yeni Prihatin Miftahul Jannah; Uril Bahruddin (Institut Agama Islam Negeri (IAIN) Kediri, 2024)
I'lal in morphology is the most important part of linguistics that the Arabic scholars have paid great attention to in the past and present, because of its accuracy and complexity of the problem. This study aims to (1) find out the forms of I'lal in Surat An-Nur, (2) find out how to use them in learning morphology, (3) find out the supporting factors for the I'lal learning process. This study uses a qualitative approach with a descriptive method. The results of this study are as follows: (1) I'lal in Surat An-Nur there are 47 words, in detail: 20 words I'lal bi Al-Qolb, 12 words I'lal bi Al-Hadf, 8 words I'lal bi An-Naqli, 4 words I'lal bi At-Taskin and 1 word I'lal bi An-Naqli wa Al-Qolb, and two words I'lal bi Al-Qolb wa Al-Hadf, (2) Benefits of knowing the forms of I'lal in the teaching of morphology is to make it easier for teachers to teach I'lal rules with models from these words, and to make it easier for students to understand morphology, especially I'lal rules, (3) The factors that support the I'lal teaching process are recognizing the origin the letters of the letters 'illah and their substitutions from one letter to another, recognize the substitution of the letter sahih from the letter mu'tal, and recognize the morphological origin of the word, especially when turning hamzah into ya' or waw, and recognize the displacement of the vowel from the letter ' illah to saheeh letters, and recognize the omitted 'illah letter, making it easier to know the wazn of a sentence. The conclusion is that this study increases Arabic language learners’ understanding of the reasoning by reading the examples in Surat Al-Nur, and it also increases morphology teachers’ understanding of the method of teaching the reasoning.